Economic changes among village households - Hazell, Peter B. R.; Ramasamy, C.; Rajagopalan, Balaji; Aiyasamy, P. K.; Bliven, Neal (International Food Policy Research Institute, 1991)
In this chapter we use the village household survey data to quantify the effects of the green revolution on farm production, income, and employment; the changes in family income and consumption of farm and nonfarm households; and the changes in the distribution of land. There are four problems with the data set that complicate our task.